Customer perception towards relationship marketing practices in Takaful industry - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (2013)
In certain business organization, acknowledging public perception towards their business practices may give a positive impact towards the future business performance. Similarly, to ensure the sustainable of Takaful industry as an alternative Islamic insurance, getting customers’ perception towards their marketing practice is important. It is so because without effective marketing practices, the Takaful products could not reach the public with the sole purpose as was planned in the earlier stage. This research thus proposes three constructs of relationship marketing and investigates the customers’ perception regarding the Takaful agents’ relationship marketing practices. It includes their Islamic ethical behaviour, product knowledge, and information communication. To achieve these objectives, this research adopted self-administered survey questionnaire and distributed it to the Takaful customers in Klang Valley area. Result from data analysis based on SPSS version 19 regards that the public particularly Muslim in rural area not totally agreed with the relationship marketing practices of their Takaful agent. This research contributes to strengthen the Takaful industry in reaching the same level with the conventional insurance particularly their effective marketing channel.